The Role of Nogo and the Mitochondria–Endoplasmic Reticulum Unit in Pulmonary Hypertension - Sutendra, Gopinath (2011)
Pulmonary arterial hypertension (PAH) is caused by excessive proliferation of vascular cells, which occlude the lumen of pulmonary arteries (PAs) and lead to right ventricular failure. The cause of the vascular remodeling in PAH remains unknown, and the prognosis of PAH remains poor. Abnormal mitochondria in PAH PA smooth muscle cells (SMCs) suppress mitochondria-dependent apoptosis and contribute to the vascular remodeling. We hypothesized that early endoplasmic reticulum (ER) stress, which is associated with clinical triggers of PAH including hypoxia, bone morphogenetic protein receptor II mutations, and HIV/herpes simplex virus infections, explains the mitochondrial abnormalities and has a causal role in PAH. We showed in SMCs from mice that Nogo-B, a regulator of ER structure, was induced by hypoxia in SMCs of the PAs but not the systemic vasculature through activation of the ER stress–sensitive transcription factor ATF6. Nogo-B induction increased the distance between the ER and mitochondria and decreased ER-to-mitochondria phospholipid transfer and intramitochondrial calcium. In addition, we noted inhibition of calcium-sensitive mitochondrial enzymes, increased mitochondrial membrane potential, decreased mitochondrial reactive oxygen species, and decreased mitochondria-dependent apoptosis. Lack of Nogo-B in PASMCs from Nogo-A/B(−/−) mice prevented these hypoxia-induced changes in vitro and in vivo, resulting in complete resistance to PAH. Nogo-B in the serum and PAs of PAH patients was also increased. Therefore, triggers of PAH may induce Nogo-B, which disrupts the ER-mitochondria unit and suppresses apoptosis. This could rescue PASMCs from death during ER stress but enable the development of PAH through overproliferation. The disruption of the ER-mitochondria unit may be relevant to other diseases in which Nogo is implicated, such as cancer and neurodegeneration.